Spatio-temporal variation characteristics of extreme precipitation over the Dongting Lake basin. Issue 3 (27th January 2022) - Chen, Jingjing; Li, Bing; Li, Yunying; Zhou, Li; Zou, Jinming; Yao, Rong
Abstract: Using the global Moran's I and other statistical methods, the spatio-temporal variation characteristics of extreme precipitation over the Dongting Lake basin are studied based on the daily precipitation at national meteorological stations from 1960 to 2016. The results show that the spatial distribution of extreme precipitation is very uneven. The areas with the maximum of extreme precipitation are located in the Lishui River basin, the middle reaches of the Zishui River and the lower reaches of the Yuanshui River. There is more extreme precipitation on the windward slope than in the basin and the lake area. There are two typical modes for extreme precipitation after the empirical orthogonal function decomposition, namely the north–south mode and the northwest–southeast mode. The extreme precipitation event is more likely to occur in the northwestern and southeastern areas of the Hunan Province. There is an obvious spatial clustering of extreme precipitation over the Dongting Lake basin. The global Moran's I is positive. In addition, the extreme precipitation at most meteorological stations shows an increasing tendency. Also, the middle reaches of the Yuanshui River basin and the Zishui River basin have the most significant increasing tendency. The abrupt change of extreme precipitation occurred around the late 1980s. HIGHLIGHTS: A variety of statistical methods were applied to the analysis of extreme precipitation. The spatio-temporal variation characteristics of extreme precipitation over the Dongting Lake basin are studied. The threshold of extreme precipitation is calculated through the statistical theory. The time length of precipitation data has reached 57 years. The results are of great significance to the defense of extreme precipitation.